Penjadwalan Distribusi Pupuk Organik Menggunakan Metode Distribution Requirement Planning (DRP) Untuk Meminimalkan Biaya Distribusi - Rio Julfika; Zeki, Muhammad; Yusnawati, Yusnawati (Program Studi Teknik Industri, Fakultas Teknik. Universitas Samudra, 2024)
Agus Pupuk UKM is located in Suka Mulia Village, Rantau District, Aceh Tamiang Regency. the problems that arise at Agus Pupuk UKM are the delay in product delivery and the mismatch between demand and delivery, so that inventory is not controlled which results in excess and shortages in inventory at Agus Pupuk UKM. This study uses the Distribution Requirement Planning (DRP) method which aims to optimally schedule distribution in accordance with the available inventory capacity, and to minimize distribution costs at UKM Agus Fertilizer. The results obtained are the scheduling of organic fertilizer distribution for the months Jan 2023-Dec 2023 in the Bandar Pusaka and Berastagi areas and for the comparison of distribution costs before and after using the DRP method which is more optimal in distribution costs using the DRP method with a cost difference in Bandar Pusaka of Rp. 6,320.160. So that there is a decrease in distribution costs by 33%, for Berastagi the difference in distribution costs using the DRP method is Rp. 11,581.920. with a decrease in distribution costs by 45%.